2016
DOI: 10.1002/em.21996
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic mode of action predictions from a multiplexed flow cytometric assay and a machine learning approach

Abstract: Several endpoints associated with cellular responses to DNA damage as well as overt cytotoxicity were multiplexed into a miniaturized, “add and read” type flow cytometric assay. Reagents included a detergent to liberate nuclei, propidium iodide and RNase to serve as a pan-DNA dye, fluorescent antibodies against γH2AX, phospho-histone H3, and p53, and fluorescent microspheres for absolute nuclei counts. The assay was applied to TK6 cells and 67 diverse reference chemicals that served as a training set. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 56 publications
7
113
0
Order By: Relevance
“…In terms of positive controls, we recommend beginning with reference chemicals from Table , agents with relatively well known MoA that have been studied at multiple laboratories. Biomarker response profiles described here and elsewhere [Bryce et al, ] should be observed before initiating more extensive testing or beginning work with uncharacterized compounds, especially if they represent new chemical space.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of positive controls, we recommend beginning with reference chemicals from Table , agents with relatively well known MoA that have been studied at multiple laboratories. Biomarker response profiles described here and elsewhere [Bryce et al, ] should be observed before initiating more extensive testing or beginning work with uncharacterized compounds, especially if they represent new chemical space.…”
Section: Resultsmentioning
confidence: 99%
“…At each site stock photomultiplier tube detectors and associated optical filter sets were used to detect fluorescence emissions associated with the fluorochromes: FITC (i.e., FL1 in BD instrument parlance), PE (FL2), propidium iodide (FL3), and Alexa Fluor® 647 (FL4). Recommended mixing and fluidics parameters for the autosampler devices were described in Bryce et al []. Generally speaking, across the sites, 4 hr samples provided 1000 or more 2 n and greater nuclei for analysis, and 24 hr samples provided 4000 or more 2 n and greater nuclei.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations